2013
DOI: 10.1021/tx300438c
|View full text |Cite
|
Sign up to set email alerts
|

Masked Mycotoxins Are Efficiently Hydrolyzed by Human Colonic Microbiota Releasing Their Aglycones

Abstract: Fusarium mycotoxins are secondary metabolites produced by Fusarium spp. in cereals. Among them, deoxynivalenol (DON) and zearalenone (ZEN) are widespread worldwide contaminants of cereal commodities and are ranked as the most important chronic dietary risk factors. Their conjugates, known as masked mycotoxins, have been described but are still not accounted for in risk assessment studies. This study demonstrates for the first time that DON and ZEN are effectively deconjugated by the human colonic microbiota, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
128
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(142 citation statements)
references
References 21 publications
11
128
1
2
Order By: Relevance
“…While the findings of Dall'Erta et al (2013) on DON are in line with previous studies, for the ZEN14Glc this seems contradictory with the results of Veršilovskis et al (2012). When the glucosides were incubated with human intestinal bacteria, both the glucoside and sulphate of ZEN were completely degraded within 30 minutes, partly resulting in the parent mycotoxin (61 % after 30 minutes, 40 % after 24 hours) and a large number of unknown metabolites.…”
Section: Bioavailability Of Modified Mycotoxinscontrasting
confidence: 46%
“…While the findings of Dall'Erta et al (2013) on DON are in line with previous studies, for the ZEN14Glc this seems contradictory with the results of Veršilovskis et al (2012). When the glucosides were incubated with human intestinal bacteria, both the glucoside and sulphate of ZEN were completely degraded within 30 minutes, partly resulting in the parent mycotoxin (61 % after 30 minutes, 40 % after 24 hours) and a large number of unknown metabolites.…”
Section: Bioavailability Of Modified Mycotoxinscontrasting
confidence: 46%
“…These results were confirmed by De Nijs et al in a study in which two in vitro models representing the human upper GI tract, a fed digestion model and a Caco-2 transwell system, were unable to transform DON3G into DON (De Nijs et al, 2012). A study by Dall'Erta et al further supported these findings, as a salivary, gastric and duodenal step in their model proved unable to release the DON aglycone from DON3G (Dall'Erta et al, 2013). De Angelis et al evaluated bread contaminated with DON and DON3G in an in vitro digestion model, and observed an increase of DON3G in the duodenal compartment, together with a distinct decrease of DON.…”
Section: Don3gmentioning
confidence: 87%
“…In vitro data indicated that D3G can be cleaved to DON by lactic acid bacteria and human feces (Berthiller et al 2011;Dall'Erta et al 2013;Gratz et al 2013). These findings correlate well with those of Nagl et al (2012Nagl et al ( , 2014, underlining that the majority of oral administrated D3G was recovered as DON in feces.…”
Section: Figmentioning
confidence: 99%